Epigenetics and Vascular Senescence–Potential New Therapeutic Targets? - Ding, Qian; Shao, Chunhong; Rose, Peter; Zhu, Yi Zhun (Frontiers in Pharmacology, 2020)
Epigenetics is defined as heritable alterations of gene expression without changing the DNA sequence, it is mainly including DNA methylation, histone modifications, and non-coding RNAs mechanisms. Vascular aging containing both structural and functional changes in vascular and a few pathological processes are involved in the progress, such as vascular cell senescence, widespread inflammation or oxidation stress and calcification. With the increase of age, people affected by the environment are gradually accumulating, compared with genetic factors, epigenetic regulation plays a more important role in the aging-related diseases, and drugs targeting epigenetic regulation are expected to be novel treatment strategies for age-related diseases. In our previous studies, we found HDAC4, JMJD3, Fra-1, GATA4 and Smyd family might be very interesting potential pharmacological sites for regulating vascular inflammation, injury, and senescence.